Food in the Internet Age - Aspray, William; Royer, George; Ocepek, Melissa G. (SpringerBriefs in Food, Health, and Nutrition, 2013)
This book examines food in the United States in the age of the Internet. One major theme running through the book is business opportunities and failures, as well as the harms to consumers and traditional brick-and-mortar companies that occurred as entrepreneurs tried to take advantage of the Internet to create online companies related to food. The other major theme is the concept of trust online and different models used by different companies to make their web presence seem trustworthy. The book describes a number of major food companies, including AllRecipes, Betty Crocker, Cook's Illustrated, Epicurious, Groupon, OpenTable, and Yelp. The book draws on business history, food studies, and information studies for its approach.